The mediating role of religiosity in the relationship between adherence to traditional gender roles and male rape myth acceptance - Castro, Ernest Monty B. (Animo Repository, 2022)
The present study investigated the role of religiosity as a mediator in the relationship between adherence to traditional gender roles and male rape myth acceptance. Its participants were undergraduate students, ages 18 and above, from the Philippines. After gathering responses from online surveys, the researchers conducted regression analyses to examine the overall data (N = 509). Contrary to previous literature and the Gender Schema Theory, they found that religiosity does not mediate the relationship between adherence to traditional gender roles and male rape myth acceptance. Considering the differences between males and females relative to the variables they used—as evidenced by past studies—the researchers employed an independent samples t-test. They then conducted another series of regression analyses and examined the data of their male (N = 266) and female (N = 243) participants. Interestingly, results revealed that while religiosity does not mediate the relationship between adherence to traditional gender roles and acceptance of myths surrounding male rape in females, it acts as a partial mediator in males. Along with each finding, the researchers presented several implications and recommendations.